AAS-Based Multi-Media Diagnostic Approach for Evaluating Heavy Metal Contamination in the Batang Ayumi River Within the Batu Bola Landfill Influence Zone - Fatma Suryani Harahap; Nurmaini Ginting; Heni Mulyani Pohan; Benny Sofyan Samosir (Jurnal Penelitian Pendidikan IPA, 2026)
This study applies an integrated multi-media approach (river water–sediment–shallow groundwater) to assess heavy metal contamination (Pb, Cu, Cd, Fe, and Hg) along the Batang Ayumi River within the influence zone of the active Batu Bola landfill, a setting rarely evaluated in an integrated manner. Samples were collected from four stations (upstream control to downstream) and analyzed using atomic absorption spectrophotometry (AAS). Fe and Pb emerged as the most responsive indicators of landfill influence: Fe increased downstream and was reflected by accumulation in sediments, while Pb showed greater mobility in river water and nearby wells, suggesting transfer from surface transport to shallow groundwater. Cu peaked upstream, whereas Cd and Hg were relatively stable but detectable across media. Although concentrations remained below applicable standards, the spatial patterns indicate persistent environmental pressure that could intensify without improved controls. By integrating evidence across water, sediment, and groundwater, this study clarifies plausible heavy-metal migration pathways from landfill leachate—surface-water transport, sediment retention, and infiltration toward shallow aquifers—supporting targeted leachate management and long-term multi-media monitoring.